Outside influences on the water column of Cumberland Sound, Baffin Island. Issue 7 (18th July 2015) - Bedard, Jeannette M.; Vagle, Svein; Klymak, Jody M.; Williams, William J.; Curry, Beth; Lee, Craig M.
Abstract Cumberland Sound, host to a commercially viable fish population in the deepest depths, is a large embayment on the southeast coast of Baffin Island that opens to Davis Strait. Conductivity, temperature, and depth profiles were collected during three summer field seasons (2011–2013), and two moorings were deployed during 2011–2012. Within the sound, salinity increases with increasing depth while water temperature cools reaching a minimum of −1.49°C at roughly 100 m. Below 100 m, the water becomes both warmer and saltier. Temperature‐salinity curves for each year followed a similar pattern, but the entire water column in Cumberland Sound cooled from 2011 to 2012, and then warmed through the summer of 2013. Even though the sound's maximum depth is over a kilometer deeper than its sill, water in the entire sound is well oxygenated. A comparison of water masses within the sound and in Davis Strait shows that, above the sill, the sound is flooded with cold Baffin Island Current water following an intermittent geostrophic flow pattern entering the sound along the north coast and leaving along the south. Below the sill, replenishment is infrequent and includes water from both the Baffin Island Current and the West Greenland Current. Deep water replenishment occurred more frequently on spring tides, especially in the fall of 2011. Although the sound's circulation is controlled by outside currents, internal water modifying processes occur such as estuarine flow and wind‐driven mixing.